First host plant record for Chlamydatus ruficornis Knight and description of nymphs (Heteroptera: Miridae: Phylinae). Issue 1 (8th August 2022) - Clark, Aaron
Abstract: Nymphs and adults of Chlamydatus ruficornis Knight were collected in southeast Wyoming, United States of America, under monoculture mats of prostrate knotweed, Polygonum aviculare Linnaeus (Polygonaceae). Adults and instars III–V of this rarely encountered phyline were common in small open areas of bare dirt between overlapping knotweed stems. In captivity, adults and nymphs fed on knotweed stems and occasionally leaves but appeared to avoid inflorescences and seeds. This species is multivoltine and overwinters as eggs in the Laramie Range of Wyoming (elevation 1665 m). A key to the developmental stages of brachypterous nymphs and photographs of each instar are provided. The location of meso- and metafemoral trichobothria and the dorsal abdominal scent gland opening of the nymphal instars are described. A rare macropterous fifth instar is described and photographed.